Thermochemical and biochemical conversion of agricultural waste for bioenergy production: an updated review - Hafiz Muhammad Aamir Shahzad; Zukhruf Asim; Sher Jamal Khan; Fares Almomani; Khaled A. Mahmoud; Muhammad Raza Ul Mustafa; Kashif Rasool (Discover Environment, 2024)
Abstract The rapid increase in global energy demand and the depletion of fossil fuels highlight the importance of biomass as a renewable energy source. Biomass, especially agricultural by-products rich in hemicellulose, cellulose, and lignin, offers a sustainable alternative for producing fuels and value-added products. The generation of power, heat, and biofuels from biomass has gained increasing significance in today’s energy landscape. This review explores the potential of advanced biomass conversion technologies, with a focus on thermochemical and biochemical processes as key methods for optimizing agricultural waste management strategies. It examines these technologies for converting agricultural wastes into bioenergy, such as biogas, syngas, bio-oil, biochar, and digestate, while detailing their operational parameters, technological principles, and implementation prospects. While biological processes are limited by long processing times and low yields, thermochemical methods are challenged by high processing costs and temperature requirements. The review also compares the advantages and challenges of each method to assess their overall effectiveness and suitability. Further research in feedstock pretreatment, catalyst development, and system optimization is essential for advancing biofuel production.